Вы находитесь на странице: 1из 15

LECTURE NOTES

EMT 2502 VIBRATIONS


MECHATRONIC ENGINEERING
Y5 S1
DeKUT

By
Inno Odira


c Copyright by Inno Odira, 2018
Table of Contents

Table of Contents iii

1 Single degree of freedom systems (SDOF) 1


1.1 Undamped Natural frequency ωn : . . . . . . . . . . . . . . . . . . . . . . . . 1
1.2 Damping ratio ζ: . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 4
1.3 Undamped free vibrations . . . . . . . . . . . . . . . . . . . . . . . . . . . . 6
1.4 Overdamped . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 8
1.5 Critically damped . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 9
1.6 Underdamped-oscillatory . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 10
1.7 Logarithmic decrement . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 11

Bibliography 13

REFERENCES 13

iii
Chapter 1

Single degree of freedom systems


(SDOF)

• SDOF is any Single mode vibration or vibration characterised with one natural fre-
quency

• Practically most of vibration systems are MDOF but can be analysed as combined
several SDOF system, therefore understanding SDOF system is imperative for the
establishment of vibrations vocabulary and analysis .

• Vibration problems focuses on the solution of differential equations of equations of


motion (EOM) of vibrating system which is equivalent to finding time history of motion
of a vibrating system.

1.1 Undamped Natural frequency ωn:


Free vibrations are oscillations about a systems equilibrium position that occur in the ab-
sence of an external excitation. Free vibrations are a result of a kinetic energy imparted to
the system or of a displacement from the equilibrium position that leads to a difference in
potential energy from the systems equilibrium position. In a another way free vibrations are
due to initial conditions.

We consider Undamped free vibration Classical Example:Mass - Spring System Fig.1.1

The differential equation governing this SDOF system have the form

mẍ + kx = 0 (1.1)

The solution of this homogenous differential equation could take any of the following

1
2

Figure 1.1: Block of mass m sliding without friction along a horizontal surface connected to
a linear spring.

forms:

x(t) = A1 cos(ωt)
x(t) = B1 sin(ωt)

Leading to a more generalised form

x(t) = A1 cos(ωt) + B1 sin(ωt)

Which after using trigonometric identities is equivalent to a more intuitive form

x(t) = A cos(ωt − φ)

After applying Euler’s equation, Leads to the form

x(t) = Aeiωt

Where A1 , B1 , A and φ depends on the initial conditions

Considering the more generalised solution take the form

x(t) = A1 cos(ωt) + B1 sin(ωt) (1.2)

Then
ẋ(t) = −A1 ω sin(ωt) + B1 ω cos(ωt) (1.3)
And

ẍ(t) = −A1 ω 2 cos(ωt) − B1 ω 2 sin(ωt) = −ω 2 (A1 cos(ωt) + B1 sin(ωt)) (1.4)


Plug equation 1.2 and 1.4 into EOM 1.1 to obtain
3

(−mω 2 + k)[A1 cos(ωt) + B1 sin(ωt)] = 0 (1.5)


Where A1 cos(ωt) + B1 sin(ωt) 6= 0
Thus −mω 2 + k = 0
Resulting in r
k
ωn = (1.6)
m
Where ωn is the Undamped natural frequency .

This occur in the absence of any forcing and is as a result of an initial potential or kinetic
energy present in the system at t = 0. These may be described by the initial displacement
from the equilibrium x0 and initial velocity v0 .
Let x0 = x(t = 0) and v0 = ẋ(t = 0) and solving for the constants A1 and B1 results in

A1 = x0
v0
B1 =
ωn
The the response of the system is given by
v0
x(t) = x0 cos(ωn t) + sin(ωn t) (1.7)
ωn
Using trigonometrical identities, 1.7 can be written as

x(t) = A cos(ωn t − φ) (1.8)

Where r
v0
A = x20 + ( )2
ωn
And
B1 v0
φ = tan−1 ( ) = tan−1 ( )
A1 x0 ωn
Eulers identity equation states

eiθ = cos θ + i sin θ (1.9)

Then A cos(ωn t − φ) = Real part of [Aei(ωn t−φ) ]

Notion of Phase angle: Phase lag

φ = ωn ∆τ
4

Figure 1.2: Notion of Phase angle in free response of an undamped system on ωt scale.

Figure 1.3: Notion of Phase angle in free response of an undamped system on time scale.

1.2 Damping ratio ζ:


We consider Damped free SDOF vibrations Classical Example:Mass - Spring - Damper
System. Fig.1.4

The Equation of motion is given by

mẍ + cẋ + kx = 0 (1.10)


Let the solution of this equation take the form

x = Aest
5

Figure 1.4: Block of mass m sliding without friction along a horizontal surface connected to
a linear spring and damper.

Then

ẋ = Asest
ẍ = As2 est

Plug these in the EOM 1.10

mAs2 est + bAsest + kAest = 0 Giving


(ms2 + bs + k)Aest = 0
(ms2 + bs + k) = 0
b k
(s2 + s+ )=0
m m
(1.11)

Solving the quadratic equation 1.11


r
−b b2 k
s1,2 = ± 2
− (1.12)
2m 4m m
k
Knowing that m
= ωn2

Then in terms of ωn Equation 1.12 becomes


r
b b 2
s1,2 = −( )ωn ± ωn ( ) −1 (1.13)
2mωn 2mωn
Where
b
ζ= ⇒ Damping ratio
2mωn
6
Thus Equation 1.13 becomes
p
s1,2 = −ζωn ± ωn ζ2 − 1 (1.14)

The form of this solution of this differential equation depends upon the values of s, which
varies with ζ . The mathematical form of the solution is different for each case. Defining

i = −1, there are four cases.

1.3 Undamped free vibrations


When ζ = 0 the roots are purely imaginary, as s = ±iωn . The free vibrations are undamped.
The general solution is a linear combination of all possible solutions, thus

x(t) = B1 eiωn t + B2 e−iωn t (1.15)


where B1 and B2 are constants of integration.
Eulers identity states
eiθ = cos θ + i sin θ
Application of Eulers identity to Equation (1.15) leads to

x(t) = B1 (cos ωn t + i sin ωn t) + B2 (cos ωn t − i sin ωn t) (1.16)


or

x(t) = C1 cos ωn t + C2 sin ωn t (1.17)


where C1 = B1 + B2 and C2 = i(B1 − B2 ) are redefined constants of integration. As
defined, C1 and C2 are real, while B1 and B2 are complex conjugates. Substituting the initial
conditions, x0 = x(t = 0) and v0 = ẋ(t = 0), into Equation (1.17) leads to

v0
x(t) = x0 cos ωn t + sin ωn t (1.18)
ωn
An alternate form of Equation (1.17) is

x(t) = A sin(ωn t + φ) (1.19)


The A sin(ωn t + φ) = imaginary part of [Aei(ωn t+φ) ]

Or

Expanding Equation (1.19) using the trigonometric identity for the sine of the sum of
angles
7

sin(a + b) = sin a cos b + cos a sin b (1.20)


gives

x(t) = A cos φ sin ωn t + A sin φ cos ωn t (1.21)


Equating coefficients of like trigonometric terms of Equations (1.18) and (1.21) leads to
s  2
ẋ0
A= x20 + (1.22)
ωn
and  
−1 ωn x0
φ = tan (1.23)
ẋ0
Equation (1.19) is an example of the simple harmonic motion . The amplitude of the
motion is A, the frequency is ωn , its phase is φ, and its period is ω2πn . The parameter ωn is
called the natural frequency, because it is the frequency at which the undamped free response
occurs naturally.
An alternate and more instructive form of Equation (1.17) is

x(t) = A cos(ωn t − φ) (1.24)


Where r
v0
A = x20 + ( )2
ωn
And
B1 v0
φ = tan−1 ( ) = tan−1 ( )
A1 x0 ωn
Eulers identity equation states

eiθ = cos θ + i sin θ (1.25)

Then A cos(ωn t − φ) = Real part of [Aei(ωn t−φ) ]

The undamped motion of a SDOF system is simple harmonic motion. The initial con-
ditions determine the energy initially present in the system. Potential energy is converted
to kinetic energy and vice versa without dissipation. Since energy is conserved, the system
eventually returns to its initial state with the original potential and kinetic energies, com-
pleting one full cycle of motion. The subsequent cycle duplicates the first cycle. The system
takes the same amount of time to execute the second cycle as it does the first. Since no
energy is dissipated, it executes subsequent cycles in the same amount of time. Thus, the
motion is cyclic and periodic. Figure 1.5 illustrates simple harmonic motion of an undamped
SDOF system.
8

Figure 1.5: Illustration of free response of an undamped system. The motion is cyclic and
periodic.

The amplitude A, defined by Equation (1.22), is the maximum displacement from equilib-
rium. The amplitude is a function of the system parameters and the initial conditions. The
amplitude is a measure of the energy imparted to the system through the initial conditions.
For a linear system
s
2E
A= (1.26)
keq
where E is the sum of kinetic and potential energies.
The phase angle , calculated from Equation (1.23) is an indication of the lead or lag
between the response and a pure sinusoidal response. The response is purely sinusoidal with
φ = 0 if x0 = 0. The response leads a pure sinusoidal response by π2 rad if ẋ0 = 0 . The
system takes a time of
(
π−φ
ωn
φ>0
t= (1.27)
− ωφn φ≤0
to reach its equilibrium position from its initial position.

1.4 Overdamped
When ζ > 1 the characteristic equation has two real roots .
p
s1,2 = ωn (−ζ ± ζ 2 − 1)
9
and the response is nonoscillatory.

x(t) = C1 es1 + C2 es2

Figure 1.6: Overdamped system on t scale.

1.5 Critically damped


When ζ = 1 the characteristic equation has only one real root, α = −ωn . The free vibrations
are critically damped.
s1,2 = −ωn t
Response given by
x = C1 e−ωn t + C2 te−ωn t
Alternately

x(t) = (C1 + tC2 )e−ζωn t

Figure 1.7: Critically damped system on t scale.


10
1.6 Underdamped-oscillatory
When 0 < ζ < 1, the roots are complex conjugates, as
p
s1,2 = −ζωn ± iωn 1 − ζ 2 = −ζωn ± iωd

.
Where
p
ωd = ωn 1 − ζ2 = Damped natural frequency
The response can be expressed as

x(t) = e−ζωn t C1 eiωd t + C2 e−iωd t


 
(1.28)

The term within the square brackets of equation 1.28 has to be real because it represents
the time response of a real physical system. It follows that C1 and C2 , as well, have to be
complex conjugates.
Note

eiωd t = cos(ωd t) + i sin(ωd t)


e−iωd t = cos(ωd t) − i sin(ωd t)

Thus , an alternative form of the general solution would be

x(t) = e−ζωn t [A1 cos(ωd t) + B1 sin(ωd t)] (1.29)

Here, A1 and B1 are the two unknown constants. By equating the coefficients, it can be
shown that

A1 = C1 + C2
B1 = i(C1 − C2 )

Hence

1
C1 = (A1 − iB1 )
2
1
C2 = (A1 + iB1 )
2
Which are complex conjugates as required.
In terms of initial conditions: Let x0 = x(t = 0) and v0 = ẋ(t = 0) as before
Then

x0 = A1
v0 = −ζωn A1 + ωd B1
11
And
v0 ζωn x0
B1 = +
ωd ωd
Yet, another form of the solution would be:

x(t) = Ae−ζωn t cos(ωd t − φ) (1.30)


Yet again, another form of the solution would be:

x(t) = Ae−ζωn t sin(ωd t + φ) (1.31)

Here, A and φ are the unknown constants with

q
A = A21 + B12
A1
φ = tan−1
B1

Figure 1.8: Underdamped system on t scale.

1.7 Logarithmic decrement


The damping ratio ζ can be experimentally determined from the free response by the log-
arithmic decrement method. To illustrate this approach, note from equation 1.31 that the
period of damped oscillations is


T = (1.32)
ωd
Also, from equation 1.31

x(t) Ae−ζωn t sin(ωd t + φ)


=
x(t + nT ) Ae−ζωn (t+nT ) sin[ωd (t + nT ) + φ]
But, sin[ωd (t + nT ) + φ] = [sin(ωd (t + nT ) + φ + 2nπ] = sin(ωd + φ)
12

Figure 1.9: Free vibrations of an under-damped SDOF system decay exponentially.

Hence
x(t) e−ζωn
= −ζωn (t+nT ) = e−ζωn T (1.33)
x(t + nT ) e
Take the natural logarithm of equation (1.33), the logarithmic decrement:
 
−ζωn T x(t)
e = ln
x(t + nT )
But , ωn T = ωn √2π = √2π 2
ωn 1−ζ 2 1−ζ
x(t)
Hence, with x(t+nT )
= r, one has the logarithmic decrement

2πnζ
p = ln r
1 − ζ2
Note that 12 ln r is the ’per cycle’ logarithmic decrement, and 1
2πn
ln r is ’per radian’
logarithmic decrement. The later is

ζ 1
p = ln r = α (1.34)
1−ζ 2 2πn
Then one has r
α2
ζ= (1.35)
1 + α2
This is the basis of the logarithmic decrement method of measuring damping. Start by
measuring a point x(t) and another point x(t + nT ) at n cycles later. For high accuracy,
pick the peak points of the response curve for the measurement of x(t) and x(t + nT ).
From equation (1.34), it is clear that for small damping, ζ = α = per-radian logarithmic
decrement.
REFERENCES

13